Etiology, clinical presentation, and outcome of temporomandibular joint luxation in cats: 21 cases (2000–2018) - Jung, Jin W.; Castejón-González, Ana C.; Stefanovski, Darko; Reiter, Alexander M. (Frontiers in Veterinary Science, 2023)
Abstract This study was performed to report etiology, clinical presentation, treatment, and outcome of temporomandibular joint (TMJ) luxation in 21 cats (2000-2018). TMJ luxation was diagnosed by either dental radiography or computed tomography (CT). Causes for TMJ luxation included altercation with a dog (38%), hit-by-car (19%), unknown (19%), fall (19%), and ran into inanimate object (5%). The most common complication was development of permanent malocclusion (24%), followed by reduced vertical mandibular range of motion (5%). Reduction of TMJ luxation was successful in 94.7% of the cases. Reduction of the TMJ luxation was significantly associated with time from injury to treatment. No other significant associations were observed between cause of injury, type of TMJ stabilization, and outcome. TMJ luxation in cats carries an excellent prognosis with early joint reduction and supportive care. Concurrent dental trauma and maxillofacial injuries are common, and all patients with head trauma must be stabilized and evaluated with a thorough examination.